The Level of Understanding of the People of Aceh Besar Regency Towards Building Approvals (PBG) - Irham, Rais Tamim; Abdullah, Abdullah; Mubarak, Mubarak (Ridwan Institute, 2025)
The transition of nomenclature and procedures from Building Permits (IMB) to Building Approvals (PBG) requires an adequate level of public understanding for policies to run effectively. In Aceh Besar Regency, the alleged low understanding has implications for permit compliance and potential legal and safety problems. This study aims to identify the level of understanding of the people of Aceh Besar Regency towards PBG. This study uses a quantitative method through the distribution of questionnaires of 100 building owners who do not have PBG, using proportionate stratified random sampling and purposive sampling techniques. The instrument used 7 indicators of comprehension measured using the Guttman scale and analyzed descriptively quantitatively. The results showed that the majority of respondents were not aware of changes in nomenclature, the obligation to manage PBG, the management mechanism through the Building Management Information System (SIMBG), the function of PBG, how to manage, where to manage, and the validity period with a mean variable level of understanding of 0.187 (category: not knowing). The practical implications of this study are that the findings show the urgent need for targeted socialization, simplification of public communication, and technical assistance programs for building owners to increase their understanding and compliance with PBG.